Human Periapical Cyst–Mesenchymal Stem Cells Differentiate Into Neuronal Cells. (June 2015) - Marrelli, M.; Paduano, F.; Tatullo, M.
It was recently reported that human periapical cysts (hPCys), a commonly occurring odontogenic cystic lesion of inflammatory origin, contain mesenchymal stem cells (MSCs) with the capacity for self-renewal and multilineage differentiation. In this study, periapical inflammatory cysts were compared with dental pulp to determine whether this tissue may be an alternative accessible tissue source of MSCs that retain the potential for neurogenic differentiation. Flow cytometry and immunofluorescence analysis indicated that hPCy-MSCs and dental pulp stem cells spontaneously expressed the neuron-specific protein β-III tubulin and the neural stem-/astrocyte-specific protein glial fibrillary acidic protein (GFAP) in their basal state before differentiation occurs. Furthermore, undifferentiated hPCy-MSCs showed a higher expression of transcripts for neuronal markers (β-III tubulin, NF-M, MAP2) and neural-related transcription factors (MSX-1, Foxa2, En-1) as compared with dental pulp stem cells. After exposure to neurogenic differentiation conditions (neural media containing epidermal growth factor [EGF], basic fibroblast growth factor [bFGF], and retinoic acid), the hPCy-MSCs showed enhanced expression of β-III tubulin and GFAP proteins, as well as increased expression of neurofilaments medium, neurofilaments heavy, and neuron-specific enolase at the transcript level. In addition, neurally differentiated hPCy-MSCs showed upregulated expression of the neural transcription factors Pitx3, Foxa2, Nurr1, and the dopamine-related genes tyrosine hydroxylase and dopamine transporter. The present study demonstrated for the first time that hPCy-MSCs have a predisposition toward the neural phenotype that is increased when exposed to neural differentiation cues, based on upregulation of a comprehensive set of proteins and genes that define neuronal cells. In conclusion, these results provide evidence that hPCy-MSCs might be another optimal source of neural/glial cells for cell-based therapies to treat neurologic diseases.